Conceptual approach to new (and not so new) types of cultural heritage - Lalana Soto, José Luis; Pérez Gil, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Cultural heritage has acquired an increasingly complex, broad and dynamic meaning. On the one hand, the old monumental paradigm has been transcended; on the other hand, heritage has spread to innumerable epistemological and practical spheres that interpret and apply it according to their interests. From a theoretical perspective, this work seeks a conceptual approach to cultural heritage through some keys that should be present in any reflection on heritage. This investigation will also be extended to the notion of Historical Urban Landscape and to the field of vernacular architecture in order to show that complexity and its real problems.